The Rebirth of the Dictatorship: its Charm and Disappointment - Aguilar, Luis F. (Revista del CLAD Reforma y Democracia, 2022)
The article focuses on the question whether the dictatorial populist governments, today appealing to multiple sectors of citizens, have really the power to solve social problems that the democratic rule of law governments seem unable to manage and solve. It describes the main characteristics of populisms of dictatorial nature and, particularly, emphasizes their decision of making exception of laws and of citizen’s rights and liberties as well, in order to rebuild the rule of law and the social policies effectiveness of the democratic regime and reinstate the social order. Since the populist authoritarian position claims to be more effective than the democratic government, producing the social results demanded by people, the question of its effectiveness is crucial. In societies crushed by any sort of needs and privations, the populism is likely to be an appraised and desirable government, but the negative effects of its unlawful decisions, subjection of public powers, harassment of dissenters and foreseeable insufficiency of resources to perform a solution of the needs, poverty and inequalities make the citizens to reassess the tradeoff they made between their liberty and submissiveness to the populist leader as long as getting a relief of its needs. The collapse of the populist authoritarian governance is its foreseeable ineffectiveness, linked to the resurgence of liberties.
Keywords: Democracy; Legitimacy; Effectiveness; Dictatorship; Public Administration; Civil Liberties